Effect of indium content on X- ray diffraction and optical constants of InxSe1-x thin films - Hasan, Bushra A. (Iraqi Journal of Physics, 2019)
Alloys of InxSe1-x were prepared by quenching technique with different In content (x=10, 20, 30, and 40). Thin films of these alloys were prepared using thermal evaporation technique under vacuum of 10-5 mbar on glass, at room temperature R.T with different thicknesses (t=300, 500 and 700 nm). The X–ray diffraction measurement for bulk InxSe1-x showed that all alloys have polycrystalline structures and the peaks for x=10 identical with Se, while for x=20, 30 and 40 were identical with the Se and InSe standard peaks. The diffraction patterns of InxSe1-x thin film show that with low In content (x=10, and 20) samples have semi crystalline structure, The increase of indium content to x=30 decreases degree of crystallinity and further increase of indium content to x=40 leads to convert structure to amorphous. Increase of thickness from 300 to 700nm increases degree of crystallinity for all indium content. Transmittance measurements were used to calculate refractive index n and the extinction coefficient k using Swanepole’s method. The optical constants such as refractive index (n), extinction coefficient (k) and dielectric constant (εr, εi) increases for low indium content samples and decreases for high indium content samples, while increase of thickness increases optical constants for all x values. The oscillator energy E0, dispersion energy Ed, and other parameters have been determined by Wemple - DiDomenico single oscillator approach.